Publicizing transgender ballet dancers: a pas de deux of inclusion and reiterative gender norms - Mandradjieff, Mara; Alterowitz, Gretchen (Feminist Media Studies, 2023)
Over the last decade, mainstream media sources from the US and UK have shown an increased interest in topics involving transgender and non-binary populations. Yet, their portrayals of such individuals tend to reaffirm rather than challenge cisnormative ideas surrounding bodies and gender. In this article, we consider this ongoing trend within the highly body-centric, traditionally-gendered artform—classical ballet. With a transgender studies and dance studies lens, we analyze current discourse surrounding the recent move for classical ballet companies and schools to adapt casting and training curricula to better include non-binary dancers. Through these analyses we reveal ways media sensationalizes the transgender body by focusing on information regarding hormone therapy and surgeries, and with the topic of ballet in mind, how this transphobic move becomes intertwined with ballet-specific processes of reshaping the body. We claim that although these popular press pieces contribute to a greater awareness of the lived experiences of transgender and non-binary dancers, they simultaneously reiterate ongoing balletic gender tropes that mark the artform as feminine and designate particular body types and movements to specific binarized genders.
Keywords: Ballet; Bibliographie; Nettoyer; gender; media; non-binary; transgender

Can Rainbow Become the New Pink? A study of ballet educators’ responses to the advancement of LGBTQ+ rights - Hawkes, Tracey (Researching Education Bulletin : Creative Arts Special Edition, 2023)
Keywords: Bibliographie; Nettoyer

Rainbow dancing in Finland and the challenge of transgender inclusion - Kavoura, Anna; Rinne, Santtu (Routledge Handbook of Gender Politics in Sport and Physical Activity, 2022)
Traditionally, partner dances occur between a woman and a man, following rather conservative gender roles and rules. However, as a result of international lesbian, gay, bisexual, transgender, intersex, queer, asexual, allies and more (LGBTIQA+) activism, some social dancing events and competitions have made space for gender and sexual diversity. This chapter focuses on the Rainbow and Same-Sex dancing scene in Finland and its potential and challenges for transgender inclusion. We draw on data collected during the first author’s ethnographic and participatory action research study on trans-inclusive sport spaces and the second author’s experiences as a professional dance teacher and Rainbow trans dancer at both same-sex and mainstream dance competitions. Our findings reveal that the Rainbow dancing movement has helped make dancing more accessible and inclusive for members of the trans community through challenging traditional cis- and heteronormative dance roles and the men-lead/women-follow paradigm. Yet, certain challenges for trans-inclusion persist, such as the transphobic politics and rules of national and international dance associations. In concluding this chapter, we provide recommendations for enhancing access and positive experiences of trans people in dance, DanceSport and sport in general.
Keywords: Bibliographie; Nettoyer

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer

Dancing Boys and Men: Negotiating Masculinity and Sexuality - Christofidou, Andria (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Theatrical dance remains widely perceived as an unconventional activity for boys and young men in many Western contexts. This chapter focuses on professional male dancers’ pathways into recreational, pre-professional dance and assesses the various obstacles encountered and the sources of encouragement available to continue dancing and to pursue a dance career. Data analysis challenges the assumption that homophobia and hierarchies among boys, men, and masculinities have been erased. The chapter argues that wider systems of inequality, oppression, and power persist. These continue to affect boys and young men, influencing their choices and the possibilities to transgress gender norms.

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

Dancing with Inclusivity: The Importance of Integrating Genderless Terminology into Swing Dance Spaces - Olander, Guinievere.R. (Unbound, 2022)
Keywords: Bibliographie; Nettoyer

A Gap in the Narrative: Exploring the Experiences of Trans Dancers Today - Best, Erica (Collège Ursinus, 2021)
Keywords: Bibliographie; Nettoyer

Super Fluid/Super Black: Translations and Teachings in Transembodied Metaphysics - Whitson, Ni’Ja (Critical Black Futures: Speculative Theories and Explorations, 2021)
Ni’Ja Whitson turns a piece that was originally commissioned as a keynote lecture for the 2020 Collegium for the African Diaspora Dance (CADD) conference, Fluid Black: Dance Back. This chapter is a hybrid text that centralizes Black Transgender and Nonbinary experiences in a conversation of futurity in African Diasporic spirituality, dance traditions, and performativities. Furthermore, Super Fluid/Super Black interrogates beingness through an exploration of astrophysics and global attempts at Black erasure to uncover new strategies of collectivizing under physical, metaphysical, and cosmic bodies that dismantle cisheteronormativity at their core.

What Makes a Lesbian Salsa Space Comfortable? Reconceptualising Safety and Homophobia - Boulila, Stefanie Claudine (Lesbian Geographies: Gender, place and power, 2015)
This chapter explores the sexual spatialisation of salsa dance spaces through the narratives of lesbian salsa dancers. It draws on conversations with seven
Keywords: Bibliographie; Nettoyer

“A Different Kind of Man”: Mediated Transgendered Subjectivity, Chaz Bono on Dancing With the Stars - Mocarski, Richard; Butler, Sim; Emmons, Betsy; Smallwood, Rachael (Journal of Communication Inquiry, 2013)
Chaz Bono’s appearance on Dancing with the Stars (DWTS) marks one of the first primetime, network appearances of a postoperative transgender person. This article deconstructs the mediated gender subjectivities of Bono as constructed by the show itself via prerecorded segments, costume and song choices, dance partner interaction, and judges’ commentaries as well as those projected by Bono during the live, unscripted portions of the show. Combining notions of the normalization of taboo sexual subjectivities through mediated contexts with lens of gender performativity, we demonstrate how transgender subjectivities are presented to a mainstream audience via such mediated choices, but also how Bono welds some agency to resist such normalization through his live performances. Bono’s appearance on DWTS stands as an important step toward acceptance of transgendered persons in mainstream society, however through a neutered, sex-free rhetoric as projected by the mediated portions of the show, his appearance is not without controversy. Additionally, we posit that Bono represents a transnormativity of a White, upper-class postoperative heterosexual male, which others all transgendered persons who fall outside of those hegemonic parallels of safe subjectivities.
Keywords: Bibliographie; Nettoyer

Negotiating the gay male stereotype in ballet and modern dance - Polasek, Katherine M.; Roper, Emily A. (Research in Dance Education, 2011)
Dance, ballet and modern in particular, is culturally defined as a feminine activity in the United States. The purpose of the present study was to examine the experiences of professional male modern and ballet dancers in the United States. Semi-structured interviews were conducted with 12 current professional ballet and modern dancers. We examined the ways in which the dancers initially became involved in dance, any support or opposition they may have confronted, and the ways in which they negotiated the stereotypical assumptions surrounding men’s involvement in dance. Four emergent themes are discussed: (1) exposure to and entrance into dance; (2) the gay stereotype; (3) negotiating the gay stereotype; and (4) homophobia within the dance community. The social significance of this study is rooted in the ways in which our culture constructs gender, the body, and movement, restricting both males and females from using and exploring their bodies in ways not deemed gender-appropriate. Attention is also given to the ways in which we can create and nurture meaningful experiences for a greater number of individuals.
Keywords: Bibliographie; Nettoyer; gay men; homophobia; male dancers; masculinity

Lesbian Lacunae: Invisible Spaces in Dance Education - Mozingo, Karen A. (Journal of Dance Education, 2005)
Recent research about sexuality and dance has begun to address the needs of gay male dancers, yet the needs of lesbian dancers have remained mostly absent from scholarly discourse. Exploring the lesbian lacunae, or invisible spaces of dance education, reveals the personal, political, and pedagogical implications of their existence within the dance community. The experiences of lesbian dancers “on the fringe” combined with new approaches to acknowledging lesbian artists and perspectives within dance history suggest the need for re-envisioning lesbian invisibility as a “liminal presence” within dance. In addition, ways dance educators can reduce the effects of heterocentrism within their institutions and celebrate the contributions of lesbian artists and educators to the field are proposed. By reconfiguring the invisibility of lesbian dancers as a liminal presence, we make visible the borders and limits of the dance profession's notions of sexuality and gender, acceptance and equality, and thereby strengthen our potential for dancing beyond them.
Keywords: Bibliographie; Nettoyer

Rehearsing Heterosexuality: "Unspoken" Truths in Dance Education - Risner, Doug (Dance Research Journal, 2002)
Keywords: Bibliographie; Nettoyer